Factors affecting selection of Islamic credit card offered by Islamic banks among HSBC Bank employees / Nur Dhiya Abdullah - Abdullah, Nur Dhiya (2012)
Islamic credit card or better known as Credit Card‐i is one of the alternative banking products introduced by Islamic financial institutions in Malaysia to substitute the conventional credit card. It acts as a tool of financial offered by many Islamic Banks. Hence, this study explored the factors affecting HSBC Bank employees’ decision in selecting Islamic credit card that is offered by Islamic banks. The Theory of Planned Behavior will be applied in order to examine the connection between individual attitude, subjective norm and perceived behavior control towards behavioral intention of using Islamic credit card. In addition to that, the analysis was done using frequency analysis, descriptive statistics, reliability analysis, Pearson Correlation Coefficient and multiple regression models for the purpose of testing the relationship between the variables. Survey data of 100 respondents from HSBC Bank were tested using these models. The result of this study has been found that only reputation of Islamic banks is the important factor towards selection of Islamic credit card whilst service quality, media awareness, social influence and religious insignificantly affect the intention of HSBC Bank employees to use Islamic credit card. This paper would offer compelling information pertaining to the factors which are highly potential in affecting HSBC Bank employees to choose Islamic credit card. Hence, the outcomes of this study would be crucial for banks managers and decision maker to structure effective strategy to contend and compete with the highly competitive banking industry in Malaysia.